Orange-fleshed sweetpotato (OFSP). Investment implementation guide - Stathers, T.; Mkumbira, J.; Low, Jan W.; Tagwireyi, J.; Munyua, H.M.; Mbabu, A.N.; Mulongo, G. (International Potato Center, 2015)
This OFSP Investment Implementation Guide is targeted at those involved in the implementation of OFSP investment programmes such as local government or NGO field staff. It provides a brief overview of the reasons for investing in pro-poor, nutrition-sensitive agricultural growth and vitamin A deficiency reduction programmes such as the promotion of OFSP. It presents a decision tool for determining where the key opportunities exist in the OFSP value chain. It then unpacks each of the investment areas in detail and presents the activities for achieving its transformation, including details on the required human, financial and physical resources. It assumes such an investment will be undertaken using a multisectoral approach.